The effects of government subsidies and environmental regulation on remanufacturing. (April 2023) - Chai, Qiangfei; Sun, Mingyao; Lai, Kee-hung; Xiao, Zhongdong
Highlights: Both the subsidy policy and CTP are able to promote remanufacturing. Technology licensing is unfavorable for remanufacturing development. Policy makers need not to worry about choosing which stakeholder to subsidize. CTP is an ideal substitution for the government subsidy policy. Abstract: It has been recognized that regulatory policies are important to promote remanufacturing. However, scant studies have evaluated and compared the performance of different regulatory policies on remanufacturing operations. This paper analyzes the effects of the government subsidy policy and the carbon cap and trade policy (CTP) on remanufacturing in a closed-loop supply chain comprising a manufacturer, an independent remanufacturer (IR), and a retailer. We develop stylized models for evaluating three subsidy policies: the IR subsidy policy, the retailer subsidy policy, and the consumer subsidy policy, develop a stylized model for assessing CTP, and incorporate technology licensing for remanufacturing into our models for analyses. We examine two issues 1) subsidizing which stakeholder is optimal and 2) whether CTP is able to replace the government subsidy policy. We compare these policies from economic, environmental, and social perspectives concerning their value for remanufacturing in closing supply chain loop. The results show that both the subsidy policy and CTP are able to promote remanufacturing. The government subsidy, the cost savings per remanufactured product, and the carbon trading price are key factors that influence the promotion of remanufacturing. Although increasing those factors can stimulate remanufacturing activity, we find that increasing the cost savings, regardless of the production cost savings or the carbon emission cost savings, should be the first option for governments and manufacturers. Based on the results of stylized models, the three subsidy policies show same performance on promoting remanufacturing, and we interpret it as an insight that government policy makers need not to worry about choosing which stakeholder to subsidize. Technology licensing is unfavorable for remanufacturing development regardless of policy types, where a lower licensing fee or the coordination between the manufacturer and IR is necessary in the process. CTP performs better or on par with the subsidy policy in most cases, suggesting that CTP is an ideal substitution for the government subsidy policy.